DESIGN OF SALES AND SERVICE INFORMATION SYSTEMS AT THE DELIMA BIKE SHOP - Ferry Aldiansah; Jasmir Jasmir; Despita Meisak (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
Delima Bike Shop is a shop that sells various bicycles and bicycle accessories. In the current system, the Delima Bike Shop in recording sales and purchase data uses writing on paper, namely notes, while stock calculations still use the traditional system using a stock book. Therefore, this study aims to design a sales and service information system using the PHP programming language, MySQL database. This research has stages, namely problem identification, literature study, problem formulation, data collection, system design and report generation. So as to produce a system that can overcome the problems that occur at the Delima Bike Shop in managing its operational activities such as data on suppliers, users, stock of goods, buying and selling, and making reports, making it easier to control data so that it helps the Delima Bike Shop in managing data to be better and orderly.